Contemporary Challenges for Caribbean Economies Crucial Problems and Practical Solutions - Yhip, Terence M.; Alagheband, Brian (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
XXXV, 446 p. 49 illus., 48 illus. in color.